(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the efficacy of sequential therapy (levofloxacin) and triple therapy (clarithromycin) in treatment of helicobacter pylori eradication. Study Design: Randomized Control Trial (RCT) Place and Duration of Study: This study was conducted at the gastroenterology department of Nishtar hospital Multan from January, 2020 to December 2020 for a period of one year. Materials and Methods: One hundred and forty diagnosed patients of H. pylori were selected for study. Patients were divided into two group ST group and TT group by lottery method. Levofloxacin and clarithromycin were used. Patients' compliance and adverse effects were compared in both groups. SPSS software with version 23 was used for data analysis. Significant probability value ≤0.05 was considered. Results: Antral gastritis, pangastritis, duodenitis, hiatus hernia and GERD of sequential group was observed as 61.4%, 25.7%, 10%, 21.4% and 45.7%, respectively. While, antral gastritis, pangastritis, duodenitis, hiatus hernia and GERD of standard group was observed as 50%, 27.1%, 15.7%, 20% and 50%, respectively. The differences were statistically insignificant. Conclusion: Sequential therapy with levofloxacin is more effective in treatment of H pylori eradication as compare to conventional triple therapy with clarithromycin. Tolerability of sequential therapy is also better than conventional triple therapy. Great resistance has found against clarithromycin in Pakistani population.